Recent progress in low-carbon binders. (August 2019) - Shi, Caijun; Qu, Bo; Provis, John L.
Abstract: The development of low-carbon binders has been recognized as a means of reducing the carbon footprint of the Portland cement industry, in response to growing global concerns over CO2 emissions from the construction sector. This paper reviews recent progress in the three most attractive low-carbon binders: alkali-activated, carbonate, and belite-ye'elimite-based binders. Alkali-activated binders/materials were reviewed at the past two ICCC congresses, so this paper focuses on some key developments of alkali-activated binders/materials since the last keynote paper was published in 2015. Recent progress on carbonate and belite-ye'elimite-based binders are also reviewed and discussed, as they are attracting more and more attention as essential alternative low-carbon cementitious materials. These classes of binders have a clear role to play in providing a sustainable future for global construction, as part of the available toolkit of cements.